(untitled) (Training and Practice : Journal of Educational Sciences, 2013)
The study shows the results of a Hungarian survey which was carried out with the help of a questionnaire filled in by 397 volunteers. The surveying was an integral part of the research conducted about the awareness-raising effect and the educational efficiency of nature trails as well as about the effectiveness of the design methodology of interpretational trails. Its primary objective was to provide a comprehensive picture concerning the attitude of Hungarian people to interpretational trails, and we also wanted to know what topics visitors are most interested in and what kinds of expectations people have in connection with nature trails.